2015
DOI: 10.1371/journal.pone.0128029
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Clusterin and Lipid Profile: A Link with Aging and Cardiovascular Diseases in a Population with a Consistent Number of Centenarians

Abstract: The role of Clusterin in attenuation of inflammation and reverse cholesterol transfer makes this molecule a potential candidate as a marker for cancer, cardiovascular disease, diabetes mellitus, and metabolic syndrome. In elderly subjects cardiovascular diseases represent the primary cause of death and different clinical studies have shown a positive correlation of these diseases with changes in the lipid pattern. This work aimed at evaluating the relationship between circulating clusterin and the biochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 57 publications
1
17
0
Order By: Relevance
“…In the present study, TC and LDL‐C were independent variables contributing to serum clusterin concentrations. In support of our results, in a recent work of 264 Sardinian individuals, clusterin was also found to be significantly related to the most atherogenic components of the lipid profile, including TC and LDL‐C . In addition, we found that participants in the highest clusterin tertiles had an increased OR for PCAD, which was especially significant in people with TC < 5.7 mmol/L and HDL‐C ≥ 1.0 mmol/L, which suggests that subjects with normal plasma lipid but higher clusterin levels may be at increased risk for PCAD.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, TC and LDL‐C were independent variables contributing to serum clusterin concentrations. In support of our results, in a recent work of 264 Sardinian individuals, clusterin was also found to be significantly related to the most atherogenic components of the lipid profile, including TC and LDL‐C . In addition, we found that participants in the highest clusterin tertiles had an increased OR for PCAD, which was especially significant in people with TC < 5.7 mmol/L and HDL‐C ≥ 1.0 mmol/L, which suggests that subjects with normal plasma lipid but higher clusterin levels may be at increased risk for PCAD.…”
Section: Discussionsupporting
confidence: 90%
“…Those proteins identified as being associated with lipid metabolism in photoaged skin in this study including apolipoprotein A and clusterin are known to be increased in plasma with age and so their increased presence may less be indicative of changes in lipid metabolism and more point to their detection in any residual blood in the tissue samples and/or increased vessel leakage in aged skin . Many of these proteins are also common to the process of ECM deposition, as previously discussed, and so their increased presence may be linked to the elastosis process rather than changes in lipid metabolism.…”
Section: Discussionmentioning
confidence: 85%
“…Clusterin can circulate in the blood as a free form or bind to lipoproteins, mainly their HDL fractions and less abundantly to LDL/VLDL [44][45][46]. Although the exact functions of clusterin are not fully understood, a number of recent studies indicate that this protein is involved in several biological processes, including apoptosis [47,48], lipid metabolism [49,50], membrane recycling, complement system regulation [51], or acts as a chaperone protein [52]. Currently, clusterin is attracting scientific attention in the context of neoplasia mechanisms as well.…”
Section: Preinfective Stage Of T Spiralis T Britovi and T Pseudomentioning
confidence: 99%